(untitled) (Journal of Hama University, 2022)
This research was carried out during 2019-2020, to set up a micropropagation protocol for Prunus. Spartioides, by using MS medium supplemented with different combination of growth regulators (BA at 1 and 2 mg/l, GA3 at 0.2 mg/l, IBA at 0.1 mg/l) in multiplication stage, and ½MS supplemented with different concentration of IBA (0.5, 1, 2 mg/l) in rooting stage. The results showed that the highest number of growths (4.66 new vegetable growth/explant) and the highest length (2.3 cm) achieved when 1mgł BA + 0.2 mgł GA3 are added to MS media. In the rooting stage, the highest rooting percentage (65%), the highest average number of roots (4.85 roots) and the highest average length of roots (3.54 cm) was obtained by adding 0.5 mg/l of IBA. Acclimatization percentage was 75%.